![a) \ 5^{x - 4} = 25\\5^{x-4} = 5^{2}\\x - 4 = 2\\x = 6 a) \ 5^{x - 4} = 25\\5^{x-4} = 5^{2}\\x - 4 = 2\\x = 6](https://tex.z-dn.net/?f=a%29%20%5C%205%5E%7Bx%20-%204%7D%20%3D%2025%5C%5C5%5E%7Bx-4%7D%20%3D%205%5E%7B2%7D%5C%5Cx%20-%204%20%3D%202%5C%5Cx%20%3D%206)
![b) \ 4^{x+1} + 4^{x} = 320\\4^{x}(4 + 1) = 320\\4^{x} \ \cdotp 5 = 320\\4^{x} = 64\\4^{x} = 4^{3}\\x = 3 b) \ 4^{x+1} + 4^{x} = 320\\4^{x}(4 + 1) = 320\\4^{x} \ \cdotp 5 = 320\\4^{x} = 64\\4^{x} = 4^{3}\\x = 3](https://tex.z-dn.net/?f=b%29%20%5C%204%5E%7Bx%2B1%7D%20%2B%204%5E%7Bx%7D%20%3D%20320%5C%5C4%5E%7Bx%7D%284%20%2B%201%29%20%3D%20320%5C%5C4%5E%7Bx%7D%20%5C%20%5Ccdotp%205%20%3D%20320%5C%5C4%5E%7Bx%7D%20%3D%2064%5C%5C4%5E%7Bx%7D%20%3D%204%5E%7B3%7D%5C%5Cx%20%3D%203)
0\\t^{2} + 2t - 8 = 0\\ t_{1} = 2; \ t_{2} \neq -4\\2^{x} = 2\\x = 1" alt="_{B}) \ 4^{x} + 2^{x+1} - 8 = 0\\2^{2x} + 2 \ \cdotp 2^{x} - 8 = 0\\t = 2^{x}, \ t > 0\\t^{2} + 2t - 8 = 0\\ t_{1} = 2; \ t_{2} \neq -4\\2^{x} = 2\\x = 1" align="absmiddle" class="latex-formula">